2006
DOI: 10.1021/je060293x
|View full text |Cite
|
Sign up to set email alerts
|

Vapor−Liquid Equilibria for the Ternary System Ethanol + Water + 1-Butyl-3-methylimidazolium Chloride and the Corresponding Binary Systems at 101.3 kPa

Abstract: In this work, experimental data of isobaric vapor-liquid equilibria for the ternary system ethanol + water + 1-butyl-3-methylimidazolium chloride ([C 4 mim][Cl]) and for the corresponding binary systems containing the ionic liquid (ethanol + [C 4 mim][Cl] and water + [C 4 mim][Cl]) were measured at 101.3 kPa. Vapor-liquid equilibria experimental data of binary and ternary systems were correlated by the NRTL equation. NRTL parameters have been used to predict the evolution of the ethanol-water azeotrope composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 8 publications
(16 reference statements)
4
94
0
1
Order By: Relevance
“…The ionic liquid concentration is stated for each curve separately from x 3 = 0 to 0.5. For comparison purposes it is also included in these figures the predicted VLE of the binary azeotropic mixture containing the ionic liquid 1-butyl-3-methylimidazolium chloride ([C 4 mim][Cl]), determined in our laboratory and previously published [8]. In Fig.…”
Section: Mim][cl] and Water + [C 6 Mim][cl] Are Listed Inmentioning
confidence: 99%
“…The ionic liquid concentration is stated for each curve separately from x 3 = 0 to 0.5. For comparison purposes it is also included in these figures the predicted VLE of the binary azeotropic mixture containing the ionic liquid 1-butyl-3-methylimidazolium chloride ([C 4 mim][Cl]), determined in our laboratory and previously published [8]. In Fig.…”
Section: Mim][cl] and Water + [C 6 Mim][cl] Are Listed Inmentioning
confidence: 99%
“…For aqueous systems with a non volatile liquid compound the measurement of vapour liquid equilibrium is the most used, but in aqueous systems containing ionic liquids it is expensive and time consuming. Not only the available equipments, developed for conventional solvents, require a large sample volume ranging from the 250 cm 3 of Wang et al [36] down to the recently reported used of a glass Fischer Labodest equilibrium still that requires a sample volume of circa 35 cm 3 [37][38][39][40][41][42][43]. Moreover the high viscosity of the mixtures rich in ionic liquid difficult a regular boiling of the mixture, what causes long equilibration times, easily reaching 6 h. To overcome these limitations we have recently reported a microebulliometer of just 8 cm 3 of capacity to study these systems [44].…”
Section: Introductionmentioning
confidence: 99%
“…The use of ionic liquids (ILs) as entrainers for extractive distillation of azeotropic or close boiling mixtures was first proposed in 2001 [1] and has been studied by several authors [2][3][4][5][6][7][8]. Due to the great diversity of structure and property, selection of ILs for the separation of specific mixture is difficult but essential for best engineering performance.…”
Section: Introductionmentioning
confidence: 99%